Islam and English language teaching: A critical literature review: Research Article - Fikri Yanda (IRecall Journal, 2023)
Islam is one of the religions, after Christianity, which has been extensively discussed in terms of its connection with English language teaching. However, exploration on this is still needed to be undertaken, that not much context is discussed. This critical literature review examines how the little research on Islam and English language education has tried to overcome the challenges to discover new insights. 32 texts from 1996 to 2020 were used to explore how Islam encounters English language teaching (ELT). The analysis revealed a number of key themes within the discourses of Islam and ELT. Moving forward, we recommend that additional initiatives –further exploration of Islam-ELT relation– should be undertaken for further development.